First Estimations of Geomagnetically Induced Currents in the South of Portugal - Joana Alves Ribeiro; Fernando J. G. Pinheiro; Maria Alexandra Pais (Space Weather)
Abstract Geomagnetic storms induce electric fields in the conducting Earth, which are the source of geomagnetically induced currents (GICs) in grounded power lines. In this study, we compute time‐varying geoelectric fields induced in the southern region of the Portuguese mainland at the time of the strongest geomagnetic storms during solar cycle 24, using a plane‐wave approximation. The driving geomagnetic storm signals are obtained from series recorded at the Coimbra magnetic observatory. Magnetotelluric impedance tensors used to compute the induced electric field are obtained using a conductivity model that takes into account general features of the local lithology and the proximity to the sea. The first GIC simulations for Portugal are presented, using data from the national high voltage power network. Starting with an a priori standard uniform electric field to compute electromotive forces, we first assess the susceptibility of the power system network given only its topology and resistance parameters. For real storms, we report (i) the clustering of the horizontal geomagnetic time variation around the northwest‐southeast direction, (ii) the simulation of the effect of the western and southern coastlines of the territory over the induced electric field, and (iii) the spotting of the substations most sensitive to storms in the studied region.